Fetal and maternal outcome in oligohydramnios pregnancy (37-40 weeks) - Joshi, Suyajna D.; Banu, Ruksar; Rai, Rajeswari; G., Jayasakthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: This study is conducted to see the effects of oligohydramnios on both mother and fetus. Methods: 237 antenatal patients delivered at Department of DNB-OBG District hospital Bellari during January 2018 to December 2018 with gestational age between 37-40wks with AFI<5cms with intact membranes were studied and analyzed retrospectively for perinatal and maternal outcome. Results: Out of 237 cases with oligohydramnios with AFI <5cm studied, about 229 cases underwent LSCS (96.6%). most are primigravida about 164(69.19%), belong to age group of <25 about 181(76%). Average gestational age noted to be 38+4 weeks about 55.9% (132), NICU admission seen in 47(19.8%) of total cases. Most of the babies delivered are >2.5 kg birth weight about 144 (60.75%) of cases. New born with APGAR <7 @ 1 min seen in 36 cases (15.15%). Meconeum stained liquor seen in about 70 cases (29.5%). Conclusions: Oligohydramnios has significant correlation with increased Caesarean section for fetal distress. Oligohydramnios is associated with high rate of pregnancy complication and increased rate of NICU admission. Oligohydramnios is a frequent occurrence demanding careful evaluation, intensive fetal surveillance and proper antepartum and intrapartum care.